Social determinants of occupational injuries among US-based commercial fishermen: a systematic review - Shannon Guillot-Wright; Leonard Kuan-Pei Wang; Bibiana Toro Figueira; Mary Overcash Jones; Ruhi Maredia; Nikhita Kichili (International Journal for Equity in Health)
Abstract Background Commercial fishing is a multibillion-dollar industry that supports job growth, small- to large- businesses, and port and city revenue. The commercial fishing industry continues to be one of the most dangerous in the US, with a fatality rate nearly 40 times higher than the national average. Dangers of the fishing industry are multi-faceted and include hazardous working conditions, strenuous labor, long work hours, and harsh weather. Moreover, a vast majority of fishermen suffer from economic insecurity, including safe and affordable housing and food insecurity. Methods We followed the recommendations and standards set by the Campbell and Cochrane Equity Methods Group and the Measurement and Evidence Knowledge Network. The review covered 1992–2022 to assess the state of research and to identify new barriers of and facilitators to injury prevention among commercial fishermen using a social determinants of health lens. Results Of 292 articles identified, 27 studies met our inclusion criteria. Out of 27 articles reviewed, social determinants of health factors included the built environment, social & community factors, economic stability, health care access, and educational attainment. A major finding was the inability for fishermen to access primary care services, which was often rooted in being a low-wage, im/migrant, or transient worker, and can further escalate injuries. A secondary finding related to injury was a feedback loop where fishermen’s unsafe environments led to a culture of accepting risk and downplaying injury, which further created unsafe environments. Conclusion Our review shows how injury is connected to social factors, such as a lack of health care access, as well as political-economic factors, such as a lack of sick leave benefits.